Case Report: Late presentation of post-coronary artery bypass surgery pericardial effusion heralding mediastinitis with tracheocutaneous fistula - Idu, Muhammad; Lim, Chiw Yeh; Chua, Kim Chai (Frontiers in Cardiovascular Medicine, 2025)
Post-coronary artery bypass surgery pericardial effusions are typically self-limiting but may rarely be significant, causing pericardial tamponade. We describe a case of late post-operative pericardial effusion that required pericardiocentesis and subsequent readmission for mediastinitis with the added complication of a tracheocutaneous fistula. Our case report is the first reported instance of pericardial tamponade heralding the onset of mediastinitis. It also describes the rare complication of tracheocutaneous fistula associated with mediastinitis.